The impact of modern communication technologies on children’s behavior - GHEROUBA, Dalila (Social Sciences Journal)
Our study aims to search for the effect of modern communication technologies on children’s behavior, because some people go to the fact that children’s exposure to video films keeps them away from all contact with their reality, to adopt the characteristics of personalities with their negatives and positives, and to go in this case to the world of deviation and violence. Means of communication on children, but the nature is determined by censorship of the type of material shown on showtimes.